You would take the following steps for G = A / (1-R):
G = A / (1-R)
Multiply by (1-R):
G * (1-R) = A
Divide by G:
(1-R) = A/G
1-R = A/G
Subtract 1:
-R = (A/G) - 1
Divide By -1:
R = -((A/G) - 1)
Check Work:
Original Problem:
A = 12; R = 5
G = 12 / (1-5)
G = -3
Solving For R:
R = -((12/-3)-1)
R = 5
Therefore, R= -((A/G)-1)
(1/x) - (1/y) = (1/z) Get the left-hand side over a common denominator:- (y-x)/xy = 1/z Take the reciprocal of both sides:- z = xy / (y-x)
7 minus 1 times 0 plus 3 divided by 3 equals 8.
y=5
Sobtract 1 from minus 9 and get minus 10.
5*2-3x-1 = 0 10-3x-1 = 0 -3x = 1-10 -3x = -9 x = 3
6 divided by 11 minus 1 divided by 2 equals?
-4
(1/x) - (1/y) = (1/z) Get the left-hand side over a common denominator:- (y-x)/xy = 1/z Take the reciprocal of both sides:- z = xy / (y-x)
i think you should add them
It depends if 1 plus tan theta is divided or multiplied by 1 minus tan theta.
3 divided by 4 plus 1 divided by 2 minus 2 divided by 3
Z=153.
(-1/6) - 2/3 = -0.8333333332
7 minus 1 times 0 plus 3 divided by 3 equals 8.
X=1
find the common multiple of 4 and 480 then minus 4. Answer is 1 over 3 and N squared. Your welcome i am your saviour.
(3x + 1) = -3 (x + 2x -1) (3x + 1) = -3 (3x - 1) 3x + 1 = -9x + 3 12x = 2 6x = 1 x = 0.16666666666666666666666666666666666666666666666666666666666666666666